Posttransplant Lymphoproliferative Disease after Lung Transplantation - Isabel P. Neuringer (Clinical and Developmental Immunology)
Posttransplant lymphoproliferative disease (PTLD) after lung transplantation occurs due to immunosuppressant therapy which limits antiviral host immunity and permits Epstein-Barr viral (EBV) replication and transformation of B cells. Mechanistically, EBV survives due to latency, escape from cytotoxic T cell responses, and downregulation of host immunity to EBV. Clinical presentation of EBV may occur within the lung allograft early posttransplantation or later onset which is more likely to be disseminated. Improvements in monitoring through EBV viral load have provided a means of earlier detection; yet, sensitivity and specificity of EBV load monitoring after lung transplantation may require further optimization. Once PTLD develops, staging and tissue diagnosis are essential to appropriate histopathological classification, prognosis, and guidance for therapy. The overall paradigm to treat PTLD has evolved over the past several years and depends upon assessment of risk such as EBV-naïve status, clinical presentation, and stage and sites of disease. In general, clinical practice involves reduction in immunosuppression, anti-CD20 biologic therapy, and/or use of plasma cell inhibition, followed by chemotherapy for refractory PTLD. This paper focuses upon the immunobiology of EBV and PTLD, as well as the clinical presentation, diagnosis, prognosis, and emerging treatments for PTLD after lung transplantation.